Analysis of the Influence of Basic Infrastructure Availability on Income Inequality in Java - Muhammad Addif Rayza Nabhaani; Fitanto, Bahtiar (Journal of Development Economic and Social Studies, 2026)
Income inequality remains a structural challenge in Java Island despite its advanced infrastructure, a phenomenon known as the "Java Paradox". This study aims to analyze the influence of basic infrastructure, comprising clean water, electricity, and roads, on income inequality across 5 provinces in Java from 2014 to 2024. This study employs a quantitative approach using panel data consisting of 55 observations. The analytical method used is panel data regression with the Fixed Effect Model (FEM) approach and White Period correction to address autocorrelation issues. The results show that electricity infrastructure has a negative and significant effect on income inequality, indicating that increased electricity access effectively drives productive economic activities for low-income households. Conversely, road and clean water infrastructure were found to have a positive but insignificant effect. These findings suggest the presence of a spatial mismatch phenomenon where road development benefits have not been evenly distributed. Policy implications suggest prioritizing electricity quality as a key instrument for inclusive growth and re-evaluating road development strategies to ensure a greater impact on economic equity.